Poster 263: Distance to Neurovascular Bundle During Iliotibial Band ACL Graft Passage: A Cadaveric Study. Issue 7 (30th July 2022) - Sanchez, Mark; Gupta, Anshal; Rohde, Matthew; Ayala, Salvador; Ellis, Henry; Tompkins, Marc; Wilson, Philip; Sherman, Seth; Green, Daniel; Ganley, Theodore; Yen, Yi-Meng; Shea, Kevin; et al.
Objectives: For patients with significant growth remaining, the Micheli (iliotibial band) ACL reconstruction technique has proven to be a reliable procedure with minimal risk for growth disturbance. Recent cadaveric studies have demonstrated that graft passage over the top of the femur may bring the graft and surgical instrument close to the critical neurovascular structures. The purpose of this study was to evaluate the Micheli over-the-top, graft passage technique for ACL reconstruction using pediatric cadaveric knees, and measure the distance between surgical instrument tip and the peroneal nerve, tibial nerve, and popliteal artery. Methods: Gross dissection was performed on seventeen skeletally immature cadaveric knees (12 male and 5 female) between the ages of 4 and 12 years old. A 5.5" curved-tip hemostat clamp was used to create a path through the posterior capsule, after the posterior neurovascular structures were identified. The tip of the clamp was passed from an anterior medial portal through the notch postero-superiorly, towards the proximal lateral capsule, with the knee flexed to 90-100 degrees or more. Once passed, the clamp was positioned in the popliteal fossa and clinical photographs were taken from the posterior aspect of the dissected knee, visualizing the tip of the clamp and the neurovascular structures. A metric ruler was included in all photographs. Digital imaging software was used to measure the distance in centimeters from clamp tip to peroneal nerve laterally, and the popliteal artery and tibial nerve medially for all specimens, FIGURE 1. Distances were averaged and stratified to assess differences in age and sex FIGURE 2. Results: The average distances from clamp to neurovascular bundle were 0.875cm (range: 0.468-1.737cm), 0.968cm (range: 0.312-1.819cm), and 1.149cm (range: 0.202-2.409cm) for tibial nerve, popliteal artery and peroneal nerve, respectfully. Means were further calculated for age groups ≤8, 9-10, and 11-12 years old. The average distance from clamp tip to peroneal nerve was 1.400cm larger for 11–12-year-old patients vs. patients ≤8 after adjusting for sex (95% CI=[0.6, 2.2], p=0.005). Conclusions: Iliotibial band graft ACL reconstruction is one of the best options in the skeletally immature, as it has the lowest risk of growth plate complications and growth arrest. The neurovascular structures are very close to the path for over-the-top graft clamp placement with distances <1 cm in many subjects. When passing the graft through the posterior knee there may be greater accessibility on the lateral cortex of the knee among older patients who are closer in age to physeal closure. The current study provides detailed measurements of instrument proximity to the neurovascular bundle in the posterior compartment of the knee. This knowledge is important to help surgeons who perform the Micheli pediatric ACL reconstruction avoid damage to the nerves and vessels in this region. Careful instrument and graft passage, with awareness of proximity to critical structures, are important to reduce the risk of neurovascular injury. Figure 1. Measurements (cm) from clamp tip to neurovascular bundle structures in right Knee model. Figure 2. Average distance from clamp from tip to neurovascular bundle by age Error bars represent 95%CI, **p<0.01